Assessment of extraction in patients on oral anticoagulant therapy with and without stopping the drug - Bansal, Anupam; Pareek, Rajat; K Kardwal, Kapil; Gumber, Arvind; Singh, Gagandeep; Walia, Sheffali (Journal of Neonatal Surgery, 2025)
Background: It is controversial whether or not oral anticoagulants should be stopped before extraction in patients using them. The present study was conducted to assess cases undergoing extraction in patients on oral anticoagulant therapy with and without stopping the drug. Materials & Methods: 50 patients on oral anticoagulant therapy scheduled for dental extraction of both genderswere divided into 2 groups of 25 each. Group I patients were instructed to continue warfarin without any alteration of the dose prior to dental extractions, and group II patients were instructed to stop warfarin 3 days before extraction. Results: Out of 50 patients, 30 were males and 20 were females. Tooth extracted were incisors in 4 in group I and 5 in group II, canine 2 in group I and 6 in group II, premolar 5 in group I and 4 in group II and molars 5 in group I and 4 in group II. The difference was non- significant (P> 0.05). The mean INR was 2.6 in group I and 1.4 in group II. The difference was significant (P< 0.05). Conclusion: As long as the INR remains within the therapeutic range, post-extraction bleeding is not a significant issue for patients who continue oral anticoagulant medication without changing the dosage.